Rational design and fabrication of frame‐structured doped bismuth vanadate nanoarchitectures as a polysulfide shield to boost the performance of lithium‐sulfur batteries. (3rd April 2020) - Xie, Ruishi; Liu, Haifeng; Huang, Heyan; Pan, Xiaoqin; Chi, Fangting; Luo, Fen; Guo, Zhicheng; Guo, Baogang; Ma, Yongjun; Li, Yuanli
Summary: Lithium‐sulfur (Li‐S) battery has been evoked increasing attention due to its creditable energy density and the abundant sulfur in nature. Nevertheless, its commercialization is still hampered in virtue of the poor conductivity of sulfur and grievous polysulfide shuttling. To address these issues, in this work, we report a cost‐efficient and facile tactic to fabricate frame‐structured neodymium‐doped bismuth vanadate (BiVO4 ) nanoarchitectures, which are reasonably designed as a polysulfide shield to alleviate the shuttling effects. The synthesized nanoarchitectures exhibit typical tetragonal phase with a unique frame structure. The frame structure of BiVO4 impedes polysulfide shuttling, and supplies electronic and ionic transmission routes. Furthermore, the rational doping of neodymium within the BiVO4 nanoarchitectures can improve electric conductivity, as well as efficiently alleviate the loss of sulfur and improve activity for sulfur reduction. Benefitting from the structural feature and doping strategy, the Li‐S battery performance with a neodymium‐doped BiVO4 nanoarchitecture is significantly improved. This strategy is easily adopted for fabricating other nanostructures, providing a feasible way to design cheap and efficient battery materials. This work is further available for synergistically uniting the virtues of the frame nanoarchitectures and doping protocol to develop advanced Li‐S batteries. Abstract : Frame‐structured doped bismuth vanadate nanoarchitectures are applied as a polysulfide shield to inhibit the shuttle effect and boost the performance of lithium‐sulfur batteries.